The Role of Artificial Intelligence Anxiety and Academic Self-Efficacy on Accounting Students’ Job Finding Anxiety - AKÇAKANAT, Özen; KILIÇARSLAN, Şerife (International Journal of Contemporary Economics and Administrative Sciences, 2025)
Finding a job after graduation presents a considerable challenge for university students, particularly in underdeveloped or developing countries. Besides, the integration of artificial intelligence in this equation seems to have increased the difficulty even more. Based on this, the current study examines the effect of artificial intelligence anxiety on the job finding anxiety among university students majoring accounting. The study also examines the effect of academic self-efficacy on job finding anxiety. The data of the study were collected using the questionnaire technique by reaching 450 students studying in 4 different universities in Türkiye. The results of the study indicate that academic self-efficacy significantly decreases students’ job finding anxiety while artificial intelligence anxiety increases students’ job finding anxiety. When this interaction was evaluated in terms of the four dimensions of artificial intelligence anxiety, a significant effect was found in the artificial intelligence configuration dimension. These findings suggest that to mitigate the anxiety of accounting students regarding their professional future, it is essential to enhance their academic self-efficacy and implement awareness-raising studies on the role of artificial intelligence in the field of accounting.